2021
DOI: 10.1016/j.cell.2020.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Required Host Factors for SARS-CoV-2 Infection in Human Cells

Abstract: To better understand host-virus genetic dependencies and find potential therapeutic targets for COVID-19, we performed a genome-scale CRISPR loss-of-function screen to identify host factors required for SARS-CoV-2 viral infection of human alveolar epithelial cells. Top-ranked genes cluster into distinct pathways, including the vacuolar ATPase proton pump, Retromer, and Commander complexes. We validate these gene targets using several orthogonal methods such as CRISPR knock-out, RNA interference knock-down, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
694
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(730 citation statements)
references
References 74 publications
26
694
9
1
Order By: Relevance
“…CoV host factor discovery and validation is an active area of research, with multiple studies appearing in press and on preprint servers in recent months ( Baggen et al., 2020 ; Daniloski et al., 2020 ; Heaton et al., 2020 ; Hoffmann et al., 2020b ; Wang et al., 2020 ; Wei et al., 2020 ; Zhu et al., 2020b ). One group performed genome-wide CRISPR screens in the African green monkey kidney cell line VeroE6 and reported strong dependency on ACE2 and CTSL , consistent with our study ( Wei et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…CoV host factor discovery and validation is an active area of research, with multiple studies appearing in press and on preprint servers in recent months ( Baggen et al., 2020 ; Daniloski et al., 2020 ; Heaton et al., 2020 ; Hoffmann et al., 2020b ; Wang et al., 2020 ; Wei et al., 2020 ; Zhu et al., 2020b ). One group performed genome-wide CRISPR screens in the African green monkey kidney cell line VeroE6 and reported strong dependency on ACE2 and CTSL , consistent with our study ( Wei et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that entry of SARS-CoV-2 pseudoparticles into Calu-3 cells could be blocked using a clinically approved serine protease inhibitor (camostat mesylate) (Hoffmann et al, 2020b). In contrast, in most other cell lines (including the lung cell line A549), recent CRISPR-Cas9 screens have suggested that SARS-CoV-2 entry in cell lines appears to be mediated by endosomal cathepsins (Daniloski et al, 2020;Wang et al, 2020b;Wei et al, 2020a). These discrepancies between human lung cell lines underscore the importance of using relevant cells, such as human airway organoids (hAOs), to study SARS-CoV-2 entry.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reported immune response differences, we found vast differences in non-immune cells such as mitochondria functions, phagocytosis, and cholesterol biosynthesis, suggesting men and women have unique response trajectories after infection and latency. Both large-scale genome-wide CRISPR screenings confirmed that cholesterol synthesis is a key host response factor and targeting cholesterol synthesis using small molecules like 27-hydroxycholesterol could reduce SARS-CoV-2 infection in vitro [32][33][34] . Of note, independent of sex, younger people (<=60) have much more differentially expressed genes than older people (>60); independent of age, women tend to have more differentially expressed genes than men.…”
Section: Discussionmentioning
confidence: 98%